MANGKU: PATTERNS OF LOCAL LEADERSHIP AUTHORITY IN THE TRADITIONS OF THE SASAK PEOPLE - Hablun Ilhami (Universitas Islam Negeri (UIN) Mataram, 2022)
The development of a knowledge system that has an impact on the emergence of a modern leadership system or pattern does not necessarily shift the local leadership pattern of the community. This paper aims to explore the pattern of Mangku leadership authority in the social life of the Sasak community including the role and pattern of Mangku leadership authority. This paper is based on qualitative research with primary data sources, namely Mangku, traditional leaders and the Sasak community in general. The data obtained through the interview method is then interpreted using Max Weber's leadership approach. The results of the analysis show that the existence of Mangku in the social life of the Sasak community serves to maintain identity and examine the values ??that enter. In addition, Mangku has the authority to regulate the community and become a reference for the community in acting and making decisions. This is due to the hereditary Mangku leadership authority based on traditions and community belief systems. Given the constantly changing nature of the pattern of leadership authority, it is necessary to carry out further research with a wider reach and informants, in order to identify issues that have not been revealed.